SPECT performance evaluation on image of Yttrium 90 - Bremsstrahlung using Monte Carlo simulation. (February 2021) - Pastrana Orejuela, Carlos O.; de Assis Coelho, Francisco; Oliveira, Susie Medeiros; Souza, Sergio A.L.; Vasconcellos de Sá, Lidia; Xavier da Silva, Ademir; Torres Berdeguez, Mirta B.
Abstract: Yttrium-90 ( 90 Y) is one of the most widely used radionuclides in Nuclear Medicine practice. However, characteristic energy of this beta emitter constitutes a difficulty for dose planning using SPECT imaging. This work aimed to study bremsstrahlung X-rays effects produced by 90 Y beta particles during SPECT image acquisition using Monte Carlo code MCNPX. Several simulations were carried out to evaluate different aspects that could affect SPECT image quality, such as: collimator type, source-collimator distance and composition of each interacting material. Two configurations of 90 Y sources were simulated: a point source in several spheres of different materials (soft tissue, water, articular cartilage, and bone) and dimensions with radius ranging from 1 to 20 mm; and a uniformly distributed source in a Lucite cylindrical phantom filled with water. It was evaluated the bremsstrahlung photon emission generated inside different materials; for this was considered the number photons that passing through every different sphere's surface for each radii and material. In case of cylindrical phantom filled with water, in order to obtain the energy deposited over NaI (Tl) crystal detector; there was considered Median Energy General Purpose (MEGP) and Low Energy High Resolution (LEHR) collimators. Moreover, using TMESH routine available in the MCNPX Monte Carlo code, energy distribution images according to the collimator type and the source-collimator distance were obtained. The simulation was validated by comparing with the spectral distribution of the 90 Y bremsstrahlung X-rays obtained experimentally from an acrylic cylindrical phantom. Results corroborated the importance of Monte Carlo simulation method to evaluate a performance of SPECT image acquisition with 90 Y. The best resolution was obtained with MEGP collimator independent of source-collimator distance. Highlights: The Monte Carlo simulation validates the results obtained experimentally, showing the veracity of the MCNPX code. MCNPX mesh tally command corroborates qualitatively MEGP as best collimator resolution. Monte Carlo MCNPX code allows qualitative studies of bremsstrahlung images for Yttrium 90.